2016
DOI: 10.7554/elife.19788
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of human translesion DNA synthesis across a UV-induced DNA lesion

Abstract: Translesion DNA synthesis (TLS) during S-phase uses specialized TLS DNA polymerases to replicate a DNA lesion, allowing stringent DNA synthesis to resume beyond the offending damage. Human TLS involves the conjugation of ubiquitin to PCNA clamps encircling damaged DNA and the role of this post-translational modification is under scrutiny. A widely-accepted model purports that ubiquitinated PCNA recruits TLS polymerases such as pol η to sites of DNA damage where they may also displace a blocked replicative poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
78
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(86 citation statements)
references
References 50 publications
8
78
0
Order By: Relevance
“…4a) play key roles in TLS regulation (13, 145). Furthermore, post-translational modifications of PCNA and polymerases have been shown to influence cell cycle, replication fork movement, polymerase switch, and TLS activities (146, 147). Rev1 serves as a TLS hub and binds both TLS insertion polymerase (η, ι or κ) via RIR (Rev1 interacting region) (Fig.…”
Section: Regulation Of Tls and Sgrs Synthesismentioning
confidence: 99%
“…4a) play key roles in TLS regulation (13, 145). Furthermore, post-translational modifications of PCNA and polymerases have been shown to influence cell cycle, replication fork movement, polymerase switch, and TLS activities (146, 147). Rev1 serves as a TLS hub and binds both TLS insertion polymerase (η, ι or κ) via RIR (Rev1 interacting region) (Fig.…”
Section: Regulation Of Tls and Sgrs Synthesismentioning
confidence: 99%
“…Pol δ alone has dramatically low, if any, affinity for P/T DNA and must anchor to PCNA to efficiently replicate the lagging strand templates 49, 51, 77, 109 . At a progressing replication fork, pol δ effectively captures a PCNA ring encircling a nascent P/T junction on the lagging strand and initiates DNA synthesis 77, 109113 .…”
Section: When Two Worlds Collide: the Replisome Encountering A Uv-mentioning
confidence: 99%
“…At a progressing replication fork, pol δ effectively captures a PCNA ring encircling a nascent P/T junction on the lagging strand and initiates DNA synthesis 77, 109113 . A pol δ holoenzyme inserts dNTPs at least 3 orders of magnitude faster than pol δ dissociates from PCNA encircling DNA 109, 113 .…”
Section: When Two Worlds Collide: the Replisome Encountering A Uv-mentioning
confidence: 99%
“…These studies described a widely accepted model of the function of ubiquitinated PCNA in TLS. However, a debate on the role of PCNA ubiquitination in TLS arose from recent extensive quantitative studies by Hedglin et al (8). Their results demonstrated that monoubiquitination of PCNA did not change the binding affinity between PCNA and pol, and the subsequent TLS across a DNA lesion was also independent of PCNA monoubiquitination.…”
mentioning
confidence: 99%
“…Their results demonstrated that monoubiquitination of PCNA did not change the binding affinity between PCNA and pol, and the subsequent TLS across a DNA lesion was also independent of PCNA monoubiquitination. They proposed that PCNA monoubiquitination indirectly promotes DNA synthesis by increasing the residence time of pol within the damaged sites, likely through altering the chromatin structure around damaged sites, although further studies are needed to test this hypothesis (8).…”
mentioning
confidence: 99%